Bilateral carotid body paraganglioma: case report - Silva, Erasmo Simão da; Tozzi, Fábio Lambertini; Paiva, Flávia Helena Matta de; Sukys, Graziela de Almeida (São Paulo Medical Journal, 2000)
CONTEXT: Surgical treatment of carotid body paragangliomas is a challenge to the surgeon because of the large vascularization of the tumor, involvement of the carotid vessels and the close anatomical relationship with the cranial nerves. CASE REPORT: A 63-year-old patient was submitted to resection of two carotid body paraganglioma tumors found in the right-side and left-side carotid bodies at the bifurcation of the common carotid arteries. Two surgeries were performed at different times and neither of them presented any morbidity. Arteriography was fundamental for diagnosis of the small, asymptomatic tumor on the right side. DESIGN: Case Report